Enhanced removal of micropollutants from water using ZnCl2-modified Spirulina sp.-based biochar - Moon, Soeun; Lee, Youn Jun; Park, Seong Jik; Lee, Chang Gu (Journal of Applied Phycology, 2024)
Acetaminophen (ACT) and bisphenol A (BPA) are chemical industry micropollutants adversely affecting humans and the environment. Among various biomass, Spirulina was used to prepare pristine biochar (SB400) and ZnCl2-modified biochar (ZnSB400). The performance of different Spirulina-based adsorbents in terms of ACT and BPA adsorption was compared. The highest removal efficiency (for ACT, 67.7%; for BPA, 96.0%) was exhibited by ZnSB400 with its microporous structure (1.67 nm) and high specific surface area (235 m2 g−1). Regarding adsorption kinetics, the pseudo-second-order model was the best-fitting model (R2 > 0.98), whereas for the adsorption isotherm, the Redlich–Peterson model provided the best fit (R2 > 0.99). The efficiency in adsorbing ACT tended to decrease with temperature; in contrast, BPA did not exhibit significant changes in adsorption with temperature. The Brunauer–Emmett–Teller method and X-ray photoelectron spectroscopy results confirmed that the primary mechanisms driving the adsorption of ACT and BPA on ZnSB400 were pore filling and π–π interactions. Hence, ZnCl2-modified Spirulina biochar is a promising adsorbent capable of effectively removing both ACT and BPA from water.
Keywords: Acetaminophen; Adsorbents; Bisphenol A; Microalgae; Zinc chloride activation